Immune parameters to p67C antigen adjuvanted with ISA206VG correlate with protection against East Coast fever. Issue 11 (7th March 2018) - Lacasta, Anna; Mwalimu, Stephen; Kibwana, Elisabeth; Saya, Rosemary; Awino, Elias; Njoroge, Thomas; Poole, Jane; Ndiwa, Nicholas; Pelle, Roger; Nene, Vishvanath; Steinaa, Lucilla
Highlights: Three doses of p67C antigen generated stronger immune responses than two doses. Antibody titers and CD4 + T-cell proliferation correlated with protection against ECF. The number of doses could not be reduced from three to two without compromising the protection. Abstract: East Coast fever (ECF) is a lymphoproliferative disease caused by the tick-transmitted protozoan parasite Theileria parva . ECF is one of the most serious cattle tick-borne diseases in Sub-Saharan Africa. We have previously demonstrated that three doses of the C-terminal part of the sporozoite protein p67 (p67C) adjuvanted with ISA206VG confers partial protection against ECF at a herd level. We have tested the efficacy of two doses of this experimental vaccine, as reducing the vaccination regimen would facilitate its deployment in the field. We reconfirm that three antigen doses gave a significant level of protection to severe disease (46%, ECF score < 6) when compared with the control group, while two doses did not (23%). Animals receiving three doses of p67C developed higher antibody titers and CD4 + T-cell proliferation indices, than those which received two doses. A new panel of immune parameters were tested in order to identify factors correlating with protection: CD4 + proliferation index, total IgG, IgG1, IgG2 and IgM half maximal titers and neutralization capacity of the sera with and without complement. We show that some of the cellular and humoral immune responses provide preliminary correlates of protection.